Direct PCR for DNA barcoding of Bulbophyllum lobbii Lindl. based on rbcL sequence - Su’udi Mukhamad; Bahrul Ulum Fuad; Setyati Dwi (BIO Web of Conferences)
DNA barcoding is a molecular technique frequently used to identify or confirm a species, which involves the steps of isolation, amplification via PCR, and sequencing analysis. However, the use of lysate derived from samples after soaked and heated in TE buffer is lacking reported for this application. This study aims to provide an alternative method for PCR using lysate as template for species identification of Bulbophyllum lobbii using rbcL primers. The results show that the lysate (after heating and briefly spun) is worthy of use as a template in PCR amplification, able to produce a thick single band with appropriate amplicon size (±600 bp). Further sequencing analysis confirms that the resulting sequence is highly readable with a clear chromatogram. BLAST analysis shows high identity (100%) with Bulbophyllum lobbii (MT518983) from USA. In sum, direct PCR using lysate provides an alternative approach for rapid DNA barcoding of plant samples with promising results.